Enhanced photodynamic efficacy and efficient delivery of Rose Bengal using nanostructured poly(amidoamine) dendrimers: potential application in photodynamic therapy of cancer - Karthikeyan, Krishnamoorthy (Cancer Nanotechnol, 2011)
Photodynamic therapy (PDT) is a promising treatment methodology whereby diseased cells and tissues are destroyed by reactive oxygen species (ROS) by using a combination of light and photosensitizers (PS). The medical application of Rose Bengal (RB), photosensitizer with very good ROS generation capability, is limited due to its intrinsic toxicity and insufficient lipophilicity. In this report, we evaluate the potential of polyamidoamine (PAMAM) dendrimers in delivering RB and its phototoxic efficiency towards a model cancer cell line. The spherical, nanoscaled dendrimers could efficiently encapsulate RB and showed characteristic spectral responses. The controlled release property of dendrimer–RB formulation was clearly evident from the in vitro drug release study. ROS generation was confirmed in dendrimer–RB system upon white light illumination. Photosensitization of Dalton’s Lymphoma Ascite (DLA) cells incubated with dendrimer–RB formulation caused remarkable photocytotoxicity. Importantly, the use of dendrimer-based delivery system reduced the dark toxicity of RB. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12645-011-0019-3) contains supplementary material, which is available to authorized users.